Regulation and Function of miR-214 in Pulmonary Arterial Hypertension. (March 2016) - Stevens, Hannah C.; Deng, Lin; Grant, Jennifer S.; Pinel, Karine; Thomas, Matthew; Morrell, Nicholas W.; MacLean, Margaret R.; Baker, Andrew H.; Denby, Laura
Dysregulation of microRNAs (miRNAs) can contribute to the etiology of diseases, including pulmonary arterial hypertension (PAH). Here we investigated a potential role for the miR-214 stem loop miRNA and the closely linked miR-199a miRNAs in PAH. All 4 miRNAs were upregulated in the lung and right ventricle (RV) in mice and rats exposed to the Sugen (SU) 5416 hypoxia model of PAH. Further, expression of the miRNAs was increased in pulmonary artery smooth muscle cells exposed to transforming growth factor β1 but not BMP4. We then examined miR-214 −/− mice exposed to the SU 5416 hypoxia model of PAH or normoxic conditions and littermate controls. There were no changes in RV systolic pressure or remodeling observed between the miR-214 −/− and wild-type hypoxic groups. However, we observed a significant increase in RV hypertrophy (RVH) in hypoxic miR-214 −/− male mice compared with controls. Further, we identified that the validated miR-214 target phosphatase and tensin homolog was upregulated in miR-214 −/− mice. Thus, miR-214 stem loop loss leads to elevated RVH and may contribute to the heart failure associated with PAH.